INFLUENCE OF THE OUTER SURFACE LAYERS OF CRYSTALS ON THE X-RAY DIFFRACTION INTENSITY OF BASAL REFLECTIONS - Sakharov B.A.; Drits V.A.; Plançon A.; Lanson B. (My University, 2004)
This study presents a mathematical formalism describing diffraction effects from periodic and mixed-layer minerals in which the outer surface layers of crystals differ from layers forming the core of the crystals. XRD patterns calculated for structure models of chlorite and irregular chlorite-smectites terminated on both sides of the crystals by either brucite-like or 2:1 layers show the strong influence that different outer surface layers make on the distribution of basal reflection intensities. Simulation of the experimental XRD patterns from two chlorite samples having different Fe-content shows that in these two samples the chlorite crystals were terminated by brucite-like layers on both sides. In contrast, crystals in a corrensite sample were terminated by water molecules and exchangeable cations. The nature of diffraction effects due to outer surface layers is discussed.